Multimodality Monitoring and Evaluation of Neuro-function in Modern NICU - Liu, Liping; Yu, Wengui (Frontiers Media SA, 2020)
Clinical neurologic examination remains the cornerstone of modern neurology. However, it provides rather limited information when facing critically ill neurologic patients, especially those with altered mental status. The underlying mechanisms might include nonconvulsive seizures, cerebral hemodynamic failure, brain edema, delayed cerebral ischemia (DCI), intracranial hypertension, etc.. Most of them are invisible but detectable. Integration of various monitoring and evaluation methods have been applied in neurologic intensive care unit (NICU), to interpret electric, biochemical and physiological changes of the brain into objective data, which help physicians select patients suitable for specific interference, recognize the treatable disorders, assess the response to treatment and prevent secondary injuries. Because some progress has been made lately, it is important for clinicians in NICU to update the concepts and knowledge of multimodality monitoring and evaluation, as well as to explore what is still needed in modern NICU. In this Research Topic, we collect articles regarding monitoring methods/techniques and their application in common neurocritical diseases.